Does having women on boards create value? The impact of societal perceptions and corporate governance in emerging markets - Abdullah, Shamsul Nahar; Ku Ismail, Ku Nor Izah; Nachum, Lilach (John Wiley & Sons, 2015)
Many governments seek to impose gender equality on boards, but the consequences of doing so are not clear and could harm firms and economies.We shed light on this topic by conceptualizing the relationships as firm- and board-specific and embedded within specific contexts. The theory is developed with reference to emerging markets, and tested on Malaysian firms.We find that female directors create value for some firms and decrease it for others.The impact varies across different performance indicators, firms’ ownership, and boards’ structure.The findings call for nuanced responses in relation to women’s nominations from both governments and firms.